A Sensible Approach to Diagnosing Cardiac Aneurysms, Pseudoaneurysms and Common Mimickers. Issue 6 (November 2018) - Amin, Sagar; Hossain, Rydhwana; Jeudy, Jean; Frazier, Aletta Ann; White, Charles
Abstract : The heart can manifest a spectrum of focal convexities that range from insignificant crypts and diverticula to clinically relevant aneurysms and pseudoaneurysms. The distinction of a clinically significant lesion from a minor focal convexity can be challenging. This article outlines the various types of focal convexities on the basis of location within the heart and discusses unique morphologic and functional features to further characterize these entities. We also highlight the most critical clinical consequences of cardiac aneurysms and pseudoaneurysms such as thromboembolic events, aneurysm ruptures, intracardiac shunting, hemopericardium, and arrhythmias.